Detection of Treponema phagedenis–like antibodies in serum and bulk milk from cows with and without digital dermatitis. (January 2018) - Frössling, Jenny; Rosander, Anna; Björkman, Camilla; Näslund, Katarina; Pringle, Märit
Digital dermatitis (DD) in dairy cows is a widespread disease linked to infection with Treponema . The traditional diagnostic method is clinical inspection, which is subjective and laborious. We explored the performance of 4 different immunogenic proteins from Treponema phagedenis in a new antibody ELISA for analysis of serum or milk. Analysis of samples from 390 cows in 25 herds showed that the ELISA could distinguish the majority of cows with DD from healthy cows. By changing the cutoff and applying parallel or serial testing, high sensitivity or specificity could be achieved. The investigation indicated that aggregated test results can be useful in the assessment of a herd's DD status. In addition, analysis of bulk tank milk samples showed good agreement with results from individual cows. The test system could be useful in research on the epidemiology and immunology of DD.